Branchial and renal urea transport mechanisms in three teleost fish - McDonald, Danielle M. (My University, 2002)
Physiological and pharmacological approaches were used to characterize the pulsatile, facilitated diffusion urea transport mechanism (tUT) known from molecular evidence to be present in the gills of the facultatively ureotelic gulf toadfish (Opsanus beta). Using those findings, potential urea transport mechanisms in the kidney of the toadfish and in both excretory organs of the ammoniotelic plainfin midshipman (Porichthys notatus), closely related to the toadfish, and the ammoniotelic freshwater rainbow trout (Oncorhynchus mykiss), distantly related to the toadfish, were investigated. With respect to the gulf toadfish, the measured branchial permeabilities to urea and the urea analogues, acetamide and thiourea, were similar in the periods between pulses when tUT was not activated. During pulsatile excretion (when tUT was activated), the permeabilities of all three substances increased, however urea permeability was significantly greater than analogue permeability. This translated to a branchial clearance of urea > acetamide >> thiourea. Midshipmen and trout displayed a similar pattern of branchial urea and analogue handling, suggesting a facilitated diffusion urea transport mechanism like that of the gulf toadfish. In all three species, the movement of urea into the kidney tubule was against an apparent concentration gradient, suggesting the presence of an active transport mechanism. The secretion clearance rate (SCR) of urea, acetamide and thiourea in toadfish and midshipmen displayed a pattern where SCRthiourea > SCRurea > SCRacetamide. In contrast, the pattern of renal handling of these substances in trout was SCRurea = SCRacetamide > SCRthiourea. The difference between trout and batrachoidid fish is likely a combination of different urea transport mechanisms and different kidney morphology; the handling of urea in batrachoidid fish was not correlated with Na+ as observed in trout, and the kidneys of toadfish and midshipmen are aglomerular while the kidney of the trout is glomerular. Based on the different patterns of urea and analogue handling observed in the kidney and gill in all three species, plus the fact that urea is moving against a concentration gradient in the kidney, it is unlikely that the urea transport mechanisms in the two organs are the same. When infused with consecutive exogenous urea loads, initial plasma and urine urea concentrations steadily increased in toadfish and midshipmen. In the toadfish, there was no change in pulse frequency and only a very weak relationship between pulse size (measured as branchial excretion during pulsatile excretion of urea) and plasma urea concentration, suggesting that the branchial excretion mechanism was already saturated at normal plasma urea concentrations. In contrast, the branchial excretion rate of urea in midshipmen was linearly correlated with plasma urea concentration with no observable transport maximum. In both toadfish and midshipmen, renal urea secretion rate maintained a strong linear relationship to plasma urea levels with no observable transport maximum, suggesting that the renal secretory transport mechanism could not be saturated even at plasma levels well above normal. Further characterization of the branchial urea excretion mechanism in the trout was achieved by using an in vitro membrane vesicle preparation, isolating the basolateral membrane of the gill. Basolateral membrane vesicles (BLMV) demonstrated urea uptake with a saturable component (Km = 1.17 ± 0.43 mmol·1⁻¹; Vmax = 0.42 ± 0.08 μmol·mg protein⁻¹·h⁻¹) at low, physiologically relevant urea concentrations and a non-saturable component at urea concentrations of up to 17.5 mmol·1⁻¹ . Uptake of urea by BLMV was inhibited by the presence of the urea analogue, thiourea, was sensitive to phloretin, a potent blocker of UT-type urea transport mechanisms, and altered by temperatures above and below the temperature of acclimation. Cortisol and glucocorticoid receptors appear to be involved in the regulation of urea production in the ammoniotelic rainbow trout (Oncorhynchus mykiss). Fish implanted with cortisol alone had 3-fold greater plasma and urine urea concentrations relative to fish of all other groups, including fish with similarly high cortisol levels but implanted with RU486. In addition, a positive correlation was observed between plasma cortisol and plasma urea concentration in cortisol-implanted fish that was abolished in fish implanted with cortisol + RU486. Compared to sham-implanted fish, cortisol-treated fish had significantly elevated branchial (two-fold higher) and urinary (three-fold higher) excretion rates of urea but not ammonia. However, as branchial and renal urea clearance were unaffected, there appears to be no stimulation or inhibition of urea excretion mechanisms in the gill or kidney separate from effects due to changes in plasma urea concentrations.
Keywords: Biology; Biology